The Influence of Family Harmony on the Morality of Class Students XII - Salma Nova Dila; Joni Adison; Triyono (Global Action and Education for Society, 2026)
This research is motivated by a phenomenon in the field where some students feel neglected by their parents due to being busy with work, family members do not listen when spoken to, members do not respect each other's opinions, and conflicts still occur among family members. The objectives of this research are: 1) to describe the family harmony of the twelfth-grade students at SMA PGRI 2 Padang, 2) to describe the morals of the twelfth-grade students at SMA PGRI 2 Padang, 3) to describe the influence of family harmony on the morals of the twelfth-grade students at SMA PGRI 2 Padang. The type of this research is descriptive quantitative with a correlational approach. The population of this study consists of 55 people. The sampling technique used is total sampling with a sample size of 55 people. The instrument used in this study is a questionnaire. The instrument used in this study is a questionnaire. The data analysis technique used in this research is simple linear regression analysis. Based on the research, the following results were obtained: 1) The harmony of the twelfth-grade students at SMA PGRI 2 Padang is categorized as harmonious, 2) The morality of the twelfth-grade students at SMA PGRI 2 Padang is categorized as good, 3) The significant influence between family harmony and morality can be seen from the R Square value of 0.085, in other words, the hypothesis accepted in the study of the influence of family harmony on morality is 8.5%. Based on these findings, the researcher suggests that guidance and counseling teachers enhance morality thru various services.